Elementary Communication Games - Hadfield, Jill (England Longman, 2010)
Elementary communication games is a collection of 40 games for elementary students of english. It offers a photocopiable material , teacher's notes , language practice with real communication.
Contents.
Keywords: Language; Learning; Teaching; English - foreign language; Communication